Rising Incidence of Communal Violence in Modern India-A Matter of Concern (International Journal of Scientific Research and Management (IJSRM), 2017)
There are mainly two forms of violence; Passive and Physical. The practice of passive violence is a daily affair, consciously and unconsciously. Again, the fuel ignites the fire of physical violence. Violence word has been derived from its Sanskrit root, “himsa”, meaning injury. In the midst of hyperactive violence, the one who possess nonviolence is blessed. Blessed is the man who can perceive the law of ahimsa (nonviolence) in the midst of the raging fire of himsa all around him. To achieve communal unity, it is emphatically stressed upon by various social reformers that ethical teachings in school curriculum, as the fundamentals of ethics are common to all religions. The conflict of the creeds and religious discriminations, must be stopped. It should be preached that we must eradicate from our midst the secret pride that our religion is truer than the other religions. In modern India, if problems related to communal violence are looked upon without any biasness in a national spirit and the solutions to the communal violence are followed and implemented with a cooperative and brotherhood spirit as suggested by various social reformers from time to time, then this problem of communal violence can be curtailed down to a great extent in future